2018
DOI: 10.3389/fnins.2018.00595
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative EEG Tomography of Early Childhood Malnutrition

Abstract: The goal of this study is to identify the quantitative electroencephalographic (qEEG) signature of early childhood malnutrition [protein-energy malnutrition (PEM)]. To this end, archival digital EEG recordings of 108 participants in the Barbados Nutrition Study (BNS) were recovered and cleaned of artifacts (46 children who suffered an episode of PEM limited to the first year of life) and 62 healthy controls). The participants of the still ongoing BNS were initially enrolled in 1973, and EEGs for both groups we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
49
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(56 citation statements)
references
References 68 publications
6
49
1
Order By: Relevance
“…A complete description of the EEG procedures has been previously reported in Taboada-Crispi et al (2018). Briefly, EEGs were recorded in 1977–1978 when the BNS children were 5–11 years of age by trained staff at the Barbados Nutrition Centre, who were blinded to the child’s nutritional history.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A complete description of the EEG procedures has been previously reported in Taboada-Crispi et al (2018). Briefly, EEGs were recorded in 1977–1978 when the BNS children were 5–11 years of age by trained staff at the Barbados Nutrition Centre, who were blinded to the child’s nutritional history.…”
Section: Methodsmentioning
confidence: 99%
“…We recently recovered EEG data that was collected in BNS participants in 1977–1978 at ages 5–11 years. EEG analyses using qEEGt (Taboada-Crispi et al, 2018) showed the following results in study participants with histories of childhood malnutrition: (1) increased theta activity (3.91–5.86 Hz) in electrodes T4, O2, Pz and in the supplementary motor area (SMA); (2) decreased alpha1 (8.59–8.98 Hz) in fronto-central electrodes and sources of widespread bilateral prefrontal area; (3) increased alpha2 (11.33–12.50 Hz) in temporo-parietal electrodes as well as in sources in central-parietal areas of the right hemisphere; and (4) increased beta (13.67–18.36 Hz), in T4, T5, and P4 electrodes and decreased in bilateral occipital-temporal regions of PEM versus control groups. Earlier EEG studies in children with histories of childhood malnutrition (e.g., Bartel et al, 1979) similarly found increased slow wave rhythms (theta band), as well as decreased alpha.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bartel and colleagues (Bartel et al, 1979) studied malnourished children five to ten years after their hospitalization and confirmed that their rest EEG still had a significantly diminished alpha and increased theta and delta frequencies compared to a control group. In a recent study, brain function alterations in the resting state activity of previously malnourished 5-11 year old children of the BNS cohort were reported, namely an excess of theta, alpha2 and beta frequencies and a decrease of alpha 1, which suggest a maturational lag in cortical development (Taboada-Crispi et al, 2018). It is clear from these behavioral and EEG findings that malnutrition at a young age has important acute deleterious effects on brain function, cognition and multiple other life fonctionning aspects.…”
Section: Introductionmentioning
confidence: 98%